Analisis Pengaruh Penerapan Sistem Pengendalian Internal Terhadap Sistem Akuntansi Penggajian dan Pengupahan - Hadi Samanto (Jurnal Akuntansi dan Pajak, 2021)
Internal control is necessary to determine the correct amount of salary and wages paid to the laborer and is guaranteed that the salary and wages paid to the workers who are entitled to receive it, in addition to preventing the payment of salaries and wages to fictitious workers or the amount of salary paid is too large or incorrect. The purpose of this research is to partially and partially determine the role of organizational structure, authority system and recording procedures, and healthy practices affect payroll and wage accounting systems. The population in this study is the entire workforce PT Ardian Mulia Perkasa with a total of 39 people (based on the number of workers in early 2021), so the number of samples in this study is also as many as 39 people. The sampling method in this study used a saturated sample technique in which the entire population was used for the sample. The role of elements of organizational structure, system of authority and recording procedures, as well as healthy practices simultaneously affect the payroll accounting system and wages. This is evidenced by the results of the study that the value of significance is smaller than the level of 5% (0.000 < 0.05) and the value of F hitung is greater than the value of Ftabel (22,446 > 2.87) and the contribution of influence to the payroll accounting system and wages of 62.9% while the remaining 27.1% is influenced by other factors that are not studied. Researchers are very grateful to the company and the parties who provide the data and time to be completed on time.